Characterization of Two Complete Chloroplast Genomes in the Tribe Gnaphalieae (Asteraceae): Gene Loss or Pseudogenization of trnT-GGU and Implications for Phylogenetic Relationships - Lee, Dong-Hyuk; Cho, Won-Bum; Choi, Byoung-Hee; Lee, Jung-Hyun (Weon'ye gwahag gi'sulji, 2017)
The tribe Gnaphalieae is one of the largest and most complex in the Asteraceae family. The taxonomic delimitations of the tribe Gnaphalieae have been inferred by researchers;however, the exact relationships between it and other tribes remain in dispute, likely becauseof complicated evolutionary histories. To improve our understanding of this tribe, weinvestigated the complete chloroplast (cp) genomes of two Asian Gnaphalieae taxa, namely thatwithin Anaphalis sinica and Leontopodium leiolepis , and used this information to infer theirphylogenetic relationships and evolution. The cp genomes of A. sinica and L. leiolepis werefound to be 152,718 bp and 151,072 bp long, respectively, with gene contents and orders thatresembled those of other Asteraceae species. However, we determined that the trn T-GGU geneswithin the two Gnaphalieae cp genomes were either pseudogenized or lost. Because these genefeatures have also been identified in other Gnaphalieae genera, but not among other Asteraceaespecies, they reinforce the taxonomic boundary of the tribe Gnaphalieae as an independentgroup. Moreover, based on the trn T-GGU gene features in members of the HAP clade, wespeculate that the parental lineages of the genera Anaphalis and Pseudognaphalium have anallopolyploid origin. Thus, mutations in the trn T-GGU gene may be used in future studies asindicators of generic and/or tribal relationships. Using 52 protein-coding genes, we performeda phylogenetic analysis which further indicated that, alongside the tribes Astereae andAnthemideae, the tribe Gnaphalieae is a monophyletic taxon. We also identified 63 and 81 SSRsin L. leiolepis and A. sinica cp genomic sequences, respectively. The results described here willbe useful for inferring the evolutionary history of the tribe Gnaphalieae, and specific genomicinformation can be applied in conservation strategies for endangered edelweiss (LeontopodiumR. Br. ex Cass.) and pearly everlasting (Anaphalis DC.) species. KCI Citation Count: 6